The implications of Adverse Childhood Experiences (ACEs) research in the treatment and prevention of offending behaviour: hype or hope? - Malvaso, Catia (Frontiers in developmental and life-course criminology, 2024)
In this chapter, we consider the unintended consequences of some assumptions made about the ACEs inventory and the implications for criminal justice system policy and practice. We discuss three contestable assumptions: (1) the ACEs inventory can be used as a screening tool for assessing individual risk and directing treatment; (2) measuring experiences after they have already occurred in adulthood can inform prevention and early intervention; and (3) ACEs can explain why people experience poor outcomes later in life. From a DLC perspective, ACEs may be considered insufficient on their own in either predicting or explaining offending behaviour. However, their prevalence in justice-involved populations encourages us to think more deeply about how exposure to ACEs interacts with other criminogenic risk factors that underlie offending pathways. With its strong theoretical and empirical foundations, DLC is well-positioned to generate and translate high-quality evidence about the association between ACEs and offending behaviour that is needed to inform treatment, early intervention, and prevention efforts.